What can be learned from failed proofs of non-theorems? - Dennis, Louise Abigail; Nogueira, Pablo (Oxford University Computing Laboratory, 2005)
This paper reports an investigation into the link between failed proofs and non-theorems. It seeks to answer the question of whether anything more can be learned from a failed proof attempt than can be discovered from a counter-example. We suggest that the branch of the proof in which failure occurs can be mapped back to the segments of code that are the culprit, helping to locate the error.